Population pharmacokinetics of everolimus in patients with seizures associated with focal cortical dysplasia - Park, Jinha; Kim, Se Hee; Hahn, Jongsung; Kang, Hoon-Chul; Lee, Sang-Guk; Kim, Heung Dong; Chang, Min Jung (Frontiers in Pharmacology, 2023)
Everolimus is an inhibitor of mammalian target of rapamycin complex 1 (mTORC1). As mutations in TSC1 and TSC2 which cause partial-onset seizures associated with TSC were found from FCD Ⅱ (focal cortical dysplasia type Ⅱ) patients, the clinical trial has been performed to explore efficacy and safety of everolimus in FCD patients. However, no dosage regimen was determined to treat FCD II. To recommend optimal dose regimen for FCD patients, a population pharmacokinetic model of everolimus in FCD patients was developed.: The data of everolimus was collected from September 2017 to May 2020 in a tertial level hospital in Korea. The model was developed by using NONMEM® software version 7.4.1 (Icon Development Solutions, Ellicott City, MD, USA).Results: Population pharmacokinetics of everolimus was described as onecompartment model with first-order absorption with effect of BSA on clearance.The final model was built as follows: TVCL = 12.5 + 9.71 × (BSA/1.5), TVV = 293, TVKA = 0.585. As a result of simulation, higher dose than 7mg/m 2 is needed in patients with BSA 0.5m 2 and higher dose than 6mg/m 2 is needed in patients with BSA 0.7m 2 . Dose of 4.5mg/m 2 is enough in the population with BSA of higher than 1.5m 2 to meet target trough range, 5 -15ng/mL.Based on the developed pharmacokinetics model, the optimal dose of everolimus in practice was recommended by considering the available strengths of Afinitor disperz®, 2 mg, 3 mg, and 5 mg.